Особливості складання цифрових планів під час моніторингу лінійної частини магістральних газопроводів. - Колос, А.-Ю. С.; Котик, З. О.; Шкурченко, Ю. В. (Видавництво Національного університету «Львівська політехніка», 2000)
Основной задачей работы было создание цифровой карты линейной части магистрального газопровода “Братство” на участке Долина - Ужгород с возможностью ее просмотра и печати в соответствующих условных обозначениях. Features of composition of digital plans cameral jobs technology during monitoring of the linear part of gas pipelines. Main task of the work was creation of digital map of linear part of gas pipeline “Brotherhood” in the zone Dolyna - Uzhgorod, with the possibility of viewing it in correspondent markings.